Association Between Supply Chain Glitches and Operating Performance - Hendricks, Kevin B.; Singhal, Vinod R. (Management Science, 2005)
This paper empirically documents the association between supply chain glitches and operating performance. The results are based on a sample of 885 glitches announced by publicly traded firms. Changes in various operating performance metrics for the sample firms are compared against a sample of control firms of similar size and from similar industries. In the year leading up to the announcement, the control-adjusted mean percent changes in operating income, return on sales, and return on assets for the sample firms are −107%, −114%, and −92%, respectively. During this same period, the control-adjusted changes in the level of return on sales and return on assets are −13.78% and −2.32%, respectively. Relative to controls, firms that experience glitches report on average 6.92% lower sales growth, 10.66% higher growth in cost, and 13.88% higher growth in inventories. More importantly, firms do not quickly recover from the negative economic consequences of glitches. During the two-year time period after the glitch announcement, operating income, sales, total costs, and inventories do not improve. We also find that it does not matter who caused the glitch, what the reason was for the glitch, or what industry a firm belongs to—glitches are associated with negative operating performance across the board.